The Nguudu Barndimanmanha Project-Improving Social and Emotional Wellbeing in Aboriginal Youth Through Equine Assisted Learning - Coffin, Juli (Frontiers in Public Health, 2019)
Background: Recent statistics have painted a grim picture for Australia's Aboriginal youth, with reports of higher levels of almost every health indicator, including depression, sexual and emotional abuse, unemployment, and incarceration. Traditional western based therapies have proven to have limited effectiveness in engaging this group as they can often be culturally inappropriate. International studies have provided promising results using equine assisted learning, with a sound methodological basis underpinned by Indigenous ways of being and doing. In Australia Aboriginal people have strong historical ties to horses through their work on stations and were often considered some of the country's best horsemen and women. While equine assisted learning programs exist in Australia there are currently none catering specifically to Aboriginal youth, run and staffed by Aboriginal staff and provided in a culturally secure manner. Aims: Alternative therapy for Aboriginal youth in the areas of grief, loss, and trauma, through an equine assisted learning program that focussed on self-concept, self-regulation, self-awareness, anxiety and depression, and sense of connectedness. Methods: Participants (N = 270) aged 6–25 years old engaged in a minimum of 6-weeks of equine assisted learning. Each session was 45–50 min duration and occurred on a weekly basis. Sessions were undertaken individually, in pairs and in groups, depending on the needs of the participant and the focus of the session goals. Qualitative examination of the participants included photography to capture the lived experiences of the participants throughout the program. In addition an cultural and age appropriate adaptation of the Strength and Difficulties Questionnaire was trialed to track changes quantitively. Conclusion: We observed improvements in self-regulation, self-awareness, and socialization skills, evident from the photography recording and the questionnaire data. In addition parent and/or caregiver and teacher reported changes in behavior, self-regulation, and socialization skills were recorded.